A child's trilingual language practices in Korean, Farsi, and English: from a sustainable translanguaging perspective. Issue 4 (2nd October 2019) - Choi, Jayoung
ABSTRACT: Increased international marriages and transnational mobility have prompted more children to grow up learning more than two languages simultaneously. However, despite well-known benefits of multilingualism, helping a growing number of trilingual children to reach their full potential has been challenging in the US, as prevalent monolingual policies and biases inhibit home language maintenance and development. The current study aims to describe rich language practices of a trilingual child from birth to age six in communicating meaning across three home languages: Korean, Farsi, and English. This ethnographic study utilised the translanguaging as well as sustainable translanguaging frameworks. The findings show that the trilingual child engaged over time in complex, nuanced, and sophisticated language practices, namely translation and codeswitching, that are unique to trilingual practices. He did so to accomplish different communicative functions by meeting and contradicting needs and practices of his audiences. The study also discusses unique contributions to translanguaging research as well as important implications for home language development for immigrant parents and teachers who work with multilingual learners in schools.